Алгоритм допусков для решения задач комбинаторной оптимизации (ЗКО) - Бойко, В.В.; Гольденгорин, Б.И.; Кузьменко, В.Н. (Теорія оптимальних рішень, 2006)
The paper considers using tolerance theory for solving combinatorial optimization problems. As a result initial problem solving converts to solving a set of special problem with special data structure. The tolerance theory and data correction are used in new algorithm for solving an assignment problem. The results of computational experiments are given in comparison with results of the best methods.